Metodologi Kritik Hadis dalam Penafsiran Isu Gender dalam Al-Qur’an - Anisatul Faizah; Uswatun Hasanah (Jurnal Teologi Islam, 2025)
This study aims to critique Hadith in interpreting gender issues in the Qur'an. The results of the study found that the methodology of hadith criticism, both sanad criticism and matan criticism, is a very important instrument in interpreting Qur'anic verses on gender. Without adequate criticism, hadith can be misused to legitimize discriminatory practices against women, even though Islam, as a religion of rahmatan lil 'alamin, cannot possibly teach injustice. Understanding the historical, sociological, and cultural context in which a hadith was uttered or a verse was revealed is a necessity. Some hadith that appear patriarchal are actually responses to specific situations during the time of the Prophet Muhammad (peace be upon him) and cannot be generalized to all contexts. For example, the hadith on female leadership (QS. An-Nisa' [4]: ​​34) needs to be understood in the specific context of the collapse of the Persian Empire, not as a universal prohibition against female leadership.